2018
DOI: 10.1086/698266
|View full text |Cite
|
Sign up to set email alerts
|

Losing Reproduction: Effect of High Temperature on Female Biochemical Composition and Egg Quality in a Freshwater Crustacean with Direct Development, the Red Cherry Shrimp,Neocaridina davidi(Decapoda, Atyidae)

Abstract: Maternal provisioning is particularly important in invertebrates with abbreviated development because large energy reserves must be provided for the developing embryo. In this context, the objective of the present study was to analyze in an aquatic invertebrate with direct development the effect of temperature on female biochemical composition and reserve allocation to maturing ovaries, which determine egg quality. A decapod crustacean, the freshwater shrimp Neocaridina davidi, was used as experimental model. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 54 publications
2
14
0
Order By: Relevance
“…Protein, lipid and glycogen contents in 30‐day‐old offspring were independent of female colouration, and they were amongst the previously reported values for the species (Baliña, Temperoni, López Greco & Tropea, ; Tropea & López Greco, ). In view of these results, maternal colouration does not seem to influence offspring performance.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Protein, lipid and glycogen contents in 30‐day‐old offspring were independent of female colouration, and they were amongst the previously reported values for the species (Baliña, Temperoni, López Greco & Tropea, ; Tropea & López Greco, ). In view of these results, maternal colouration does not seem to influence offspring performance.…”
Section: Discussionsupporting
confidence: 83%
“…Protein, lipid and glycogen contents in 30-day-old offspring were independent of female colouration, and they were amongst the previously reported values for the species (Baliña, Temperoni, López Greco & Tropea, 2018;. differences were found with a diet supplemented with 400 mg/ kg (Yamada, Tanaka, Sameshima & Ito, 1990).…”
Section: Discussionsupporting
confidence: 80%
“…Furthermore, egg hatching rate and larval tolerance to ammonia were significantly improved by the inclusion of n‐3 PUFAs in the diet of M. rosenbergii broodstock, whereas fecundity increased with increasing levels of dietary LIN (C18:2 n‐6; Cavalli et al., 1999). In this species, as well as in N. davidi , n‐6 PUFAs levels in tissues were more abundant than n‐3 PUFAs (C20:5 n‐3‐ EPA‐ and C22:6 n‐3‐ DHA‐; Baliña et al., 2018). It was proposed that N. davidi females derive LIN to oocytes during vitellogenesis for its use by embryos as a DHA precursor.…”
Section: Discussionmentioning
confidence: 73%
“…The first diet was balanced food for tropical fish, which was the only one previously tested for N. davidi reproduction and growth (e.g. Baliña, Temperoni, López Greco, & Tropea, 2018; Marciano et al., 2018; Tropea & López Greco, 2015). The second one was a commercial diet specifically formulated for crustaceans with a similar market value, and the third one was a commercial diet for ornamental fish which had a lower cost than the others.…”
Section: Introductionmentioning
confidence: 99%
“…The results obtained in the present study suggested that high concentration of monounsaturated fatty acid (MUFA) with focusing in significant higher content of 16:1 (Palmitoleic) in mussel, may assist metabolic functioning and support energy requirements during the embryonic development which finally could be associated for better egg retention and high egg production compared to other diets. As mentioned by Balina et al (2018), reproductive event in broodstocks uses great amount of energy. It is broadly acknowledged that MUFA is utilized to provide energetic function (Cavalli et al, 2001;Rosa et al, 2003).…”
Section: Resultsmentioning
confidence: 99%